Unsafe Acts Among Indonesian Industrial Workers: A Descriptive Study - Saptaputra, Syawal Kamiluddin; Fikriani, Ade; Erawan, Putu Eka Meiyana (Diversity: Disease Preventive of Research Integrity, 2022)
Unsafe action is a human failure to follow the correct work requirements and procedures, causing work accidents. The aim of the study was to describe the unsafe acts of loading and unloading workers at PT. X in Kendari City. The type of study was quantitative research with a descriptive observational approach. This study only looks at the unsafe acts carried out by workers by using observation sheets in the form of checklists and questionnaires. The number of samples was determined by a total sampling of 48 people. The results of this study used the univariate analysis method, where it was found that the results of Unsafe Action, the type of unsafe action that is most often carried out by workers at was the improper use of Personal Protective Equipment. In addition, there was the operation of Lift-and-Transport equipment at speeds that are not in accordance with the SOP, as well as the arrangement of containers outside the stacking field. Loading and unloading workers who act unsafely are at high risk of work accidents that can cause injury, lost working days, and decreased productivity. It is hoped that the PT. X Kendari City to improve supervision of the use of Personal Protective Equipment (PPE) for workers as an effort to control work accidents.